New media and intercultural communication : identity, community and politics - Cheong, Pauline Hope, 1977-; Martin, Judith N.; Macfadyen, Leah P. 1971- (Leah Pauline) (New York : Peter Lang, 2012)
There is increasing awareness of the development of newer smart and more interactive media, at precipitate speed, in many parts of the world. The concept of change - as opposed to continuity - is central to the increasing interest in digital media. It offers theoretical insights, fresh evidence and rich applications as it assesses the nature of digital culture(s) in order to address assumptions about the present state of mediated global society(ies) and their future trajectory.
Ch. 1. Introduction: Mediated intercultural communication matters: understanding new media, dialectics and social change / Pauline Hope Cheong, Judith N. Martin and Leah P. Macfadyen -- Ch. 2. Designing for culture: an ecological perspective on indigenous knowledge and database design / Maja Van der Velden -- Ch. 3. A structurational interaction approach to investigating culture, identity and mediated communication / Beth Bonniwell Haslett -- Ch. 4. Exploring cultural challenges in e-learning / Bolanle A. Olaniran -- Ch. 5. Culture, context and cyberspace: rethinking identity and credibility in international virtual teams / Kirk St.Amant -- Ch. 6. Producing the self at the digital interface / Natalia Rybas -- Ch. 7. Who am I in virtual space? a dialectical approach to student's online identity expression / Ping Yang -- Ch. 8. New media and asymmetry in cultural identity negotiation / Guo-Ming Chen and Xiadong Dai -- Ch. 9. Negotiating a new identity online and off-line: the Heart NET experience / Debbie Rodan, Lynsey Uridge, Lelia Green -- Ch. 10. Inoculating against invisibility: the friendly circle of cancer patients' Chinese blog / Wei Sun, Andrew Jared Critchfield -- Ch. 11. Rite of death as a popular commodity: neoliberalism, media, and new Korean funeral culture / Joonseong Lee -- Ch. 12. Far away from home... with a mobile phone! Reconnecting and regenerating the extended familiy in Africa / Gado Alzouma -- Ch. 13. When Indian women text message: culture, identity, and emerging interpersonal norms of new media / Robert Shuter -- Ch. 14. To browse or not to browse : perceptions of the danger of the Internet by ultra-orthodox Jewish women / Azi Lev-On, Rivka Neriya-Ben Shahar -- Ch. 15. From the coffee table album to the mobile phone: a Portuguese case study / Carla Ganito, Catia Ferreira -- Ch. 16. Asian American new media communication as cultural engagement: e-mail, vlogs/blogs, mobile applications, social networks, and Youtube / Konrad Ng -- Ch. 17. Jamaica and Chile online: accessing and using the Internet in a developing world context / Nickesia Gordon, Kristin Sorensen -- Ch. 18. Cultural peculiarities of Russian audience participation in political discourse in the era of new technologies / Irina Privalova -- Ch. 19. The Vienna Unibrennt platform: hidden pitfalls of the social web / Herbert Hrachovec.
Includes bibliographical references and index.
Keywords: Intercultural communication; Mass media -- Social aspects; Digital media -- Social aspects